Hydrophobic effects are dominant over secondary orbital interactions for a simple Diels-Alder reaction in salt solutions - Sarma, D.; Kumar, Anil (Organic Letters, 2006)
The stereoselectivity ratios for a Diels-Alder reaction between cyclopentadiene with methyl trans-crotonate carried out in salt solutions demonstrate the dominance of hydrophobic effects over secondary orbital interactions.